Novel features of the nonlinear model arising in nano-ionic currents throughout microtubules - Celik, E.; Bulut, H.; Baskonus, H. M. (Indian Assoc Cultivation Science, 2018)
In this manuscript, the modified exp (-Omega(xi)-expansion function method is implemented to find the new solutions to the nonlinear differential equation being the transmission line model. We obtain some new solutions to this model such as complex, exponential, trigonometric and hyperbolic functions. We plot the two-and three-dimensional surfaces of each solutions obtained in this manuscript.
Keywords: The MEFM; Complex function; Exponential function; Trigonometric function; Hyperbolic function structures